CURRICULUM MODEL OF RELIGIOUS MODERATION AT ALMAARIF SINGOSARI TECHNOLOGY ISLAMIC BOARDING SCHOOL - Hasan, Faisal Ghufron (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Indonesia as a democratic country faces various social challenges such as conflict, disharmony and inequality. In dealing with this, Islamic teachings regarding the concept of wasathiyah (moderation) become relevant. This concept includes tawassuth (middle), i'tidal (fair), and tawazun (balanced), which, if applied, can calm various aspects of life without extremism or fanaticism. Education, especially through institutions such as Islamic boarding schools, plays an important role in teaching these values of moderation. The Islamic boarding school education system which combines a general curriculum and intensive religious education is considered effective in instilling the values of religious moderation. This research aims to identify the religious moderation curriculum model at the Almaarif Singosari Islamic Boarding School in the intensive Islamic boarding school program, understand its objectives, and its application in education. The research method used is descriptive qualitative, with data obtained through interviews, observation, and documentation. The results show that the intensive Islamic boarding school program has succeeded in integrating religious and national values, as well as forming students' characters who are moderate, tolerant, and have noble morals. It is hoped that these findings will help educational institutions, parents, and the government in understanding and implementing the religious moderation curriculum to prevent extremism and radicalism in Indonesia.